Application of foreign law in domestic courts in Europe and the challenges of legal pluralism - Jerónimo, Patrícia (2017)
The chapter looks into the way in which the debate about the application of foreign law by domestic courts in Europe, under Private International Law mechanisms (i.e. conflict-of-laws rules), intersects with another debate, also focused on what the courts are doing, about cultural diversity and legal practice, generally known as «multicultural jurisprudence» or «cultural defence» . The two debates have been going on in parallel for a long time and have come to overlap in recent years, largely due to the attention paid to what some deem to be a «dangerous Islamisation of western legal systems» resulting from the realisation that domestic courts in the West have been applying religiously inspired foreign legal provisions to the adjudication of judicial disputes. The chapter addresses the question of whether or not Private International Law mechanisms can be the answer to the multicultural jurisprudence’s quest for more judicial sensibility to cultural diversity and legal pluralism. It starts with a brief overview of some of the main arguments put forward by advocates of the cultural defence and of the accommodation of minority legal orders, and the backlash that these arguments have met, mostly due to concern for the integrity of western domestic legal systems. It will then look into the way in which foreign laws have been applied by domestic courts in Europe, under Private International Law mechanisms, to assess if (and if so, to what extent) the «openness» to foreign laws attested by judicial practice in this context can help the cause of the advocates of the cultural defence.